Chiral LC-PDA-ORD Method for The Separation of Linagliptin Enantiomers On Coated Polysaccharide Based Amylose Tris (3, 5-Dimethylphenylcarbamate) Stationary Phases - Shankar, Eegala Bheema; Naidu, Challa Gangu; Devaraju, Subramani; Marok, Satwinder S; Rao, Y. Srinivasa (International Journal of Membrane Science and Technology, 2023)
Chiral normal phase high performance liquid chromatographic (chiral-HPLC) was designed and verified for the separation of linagliptin enantiomers using coated polysaccharide chiral stationary phases. The stationary phase was amylose tris (3, 5-dimethylphenylcarbamate) (250x4.6mm, 5 µm), while the mobile phase was a mixture of 50:50:0.1% v/v. With a flow rate of 1 mL/min, orthophosphoric acid was mixed with hexane, isopropyl alcohol, and diethyl amine to achieve a pH of 5.2. The detection was seen at 225 nm. The optical rotatory dispersion (ORD) polarimeter was connected in series to the PDA outlet in order to determine the enantiomer conformation. The linagliptin retention times were found to be 5.454 and 8.772 minutes. Between 3.9 and 23.4 µg/ml, enantiomers were discovered to be linear, with a correlation coefficient of 0.9995. This method was validated in terms of linearity, LOD, LOQ, precision, accuracy, and robustness studies in accordance with ICH requirements. Novelty: The proposed analytical method for the chiral analysis of linagliptin can be used by pharmaceutical industries quality control departments.